Aspects epidemiologiques et cliniques des pemphigus au Senegal [Epidemiological and clinical aspects of pemphigus in Senegal] - Moussa Diallo; Boubacar Ahy Diatta; Aassane Diop; Maodo Ndiaye; Mame Téné Ndiaye; Birame Seck; Aminata Deh; Kadim Diop; Suzanne Niang (Our Dermatology Online, 2017)
Background: The purpose of this study was to specify the epidemiological and clinical characteristics of pemphigus in the Department of Dermatology of the University Hospital of Dakar. Patients and Methodology: All medical records of patients seen for pemphigus in our department over a 11-year period were analyzed retrospectively. Results: We collected 105 cases of pemphigus, corresponding to a frequency of 10 cases/year and a hospital prevalence of 2.7%. Thus, pemphigus held the second rank of blistering autoimmune bullous diseases after bullous pemphigoid. The mean age of patients was 47.62 years and the age group [40-59 years] was predominantly affected (28 cases; 45 %). There were 41 femeles and 21 men (F/M ratio: 2). We did not find an endemic focus in our country. Clinical forms were dominated by pemphigus foliaceus (30 cases; 48.5 %), followed by pemphigus vulguaris (19 cases; 30.6 %) and finally by pemphigus erythematosus (13 cases; 21%). In 16 cases (25 %), the pemphigus had begun after the consumption of a traditional medicinal plant (8 cases). An associated toxidermia was found in12 cases. Pruritus was present in 43 patients (69.35%). Discussion: In Senegal, pemphigus are common diseases, but without however an endemic focuc. They occur in young women, with a predominance of superficial forms, especially pemphigus foliaceus. The presence of pruritus and associated toxidermia to traditional medicinal plants are common. RÉSUMÉ Introduction: L'objectif de cette étude était de préciser les aspects épidémiologiques et cliniques des pemphigus au CHU de Dakar. Patients et Méthodes: Tous les dossiers des malades admis pour pemphigus ont été analysé de façon rétrospective sur une période de 11 ans. Résultats: Nous avons colligé 105 cas de pemphigus, correspondant à une fréquence de 10 cas/an et une prévalence hospitalière de 2,7 %. Les pemphigus occupaient le 2° rang des dermatoses bulleuses auto-immunes après la pemphigoide bulleuse. L'âge moyen des patie nts était de 47,62 ans et la tranche d'âge [40-59] ans était la plus concernée (28 cas; 45 %). Il s'agissait de 41 femmes et 21 hommes, soit un sex-ratio F/H de 2. Il n'existait pas de foyer endémique. Les formes cliniques étaient dominées par le pemphigus foliacé (30 cas; 48,5 %), suivi du pemphigus vulguaire (19 cas; 30,6 %) et enfin du pemphigus séborrhéique (13 cas; 21%). Dans 16 cas (25 %), le pemphigus avait débuté au décours d'une phytothérapie orale (8 cas). Une toxidermie surajoutée était retrouvée dans 12 cas. Le prurit était noté chez 43 patients (69,35%). Discussion: Au Sénégal, les pemphigus sont des affections fréquentes, mais sans toutefois de foyer endémique et surviennent chez des femmes jeunes, avec une prédominance des pemphigus superficiels, notamment du pemphigus foliacé. La présence d'un prurit et d'une toxidermie surajoutée aux plantes traditionnelles sont fréquentes.